2002
DOI: 10.1021/ol017229j
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Mannich-Type Reaction Catalyzed by VO(acac)2

Abstract: A facile VO(acac)(2)-catalyzed in situ generation of iminium ions from amine N-oxides and their participation in a modified Mannich-type reaction is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…Hwang and Uang have shown that a series of commercially available amine N-oxides could be converted to the corresponding iminium ion by treatment with a simple vanadium catalyst. [8] We reasoned that this strategy could be extended to tertiary tetrahydroisoquinoline N-oxides formed in situ from the parent amine (Scheme 1 b). [9] To begin our study, N-benzyl THIQ 1 was chosen as an appropriate test substrate, as the benzyl group can be potentially removed and thus allows further functionalization of the amine.…”
mentioning
confidence: 99%
“…Hwang and Uang have shown that a series of commercially available amine N-oxides could be converted to the corresponding iminium ion by treatment with a simple vanadium catalyst. [8] We reasoned that this strategy could be extended to tertiary tetrahydroisoquinoline N-oxides formed in situ from the parent amine (Scheme 1 b). [9] To begin our study, N-benzyl THIQ 1 was chosen as an appropriate test substrate, as the benzyl group can be potentially removed and thus allows further functionalization of the amine.…”
mentioning
confidence: 99%
“…To remedy this regioselectivity issue, we envisioned an activating agent for the Polonovski reaction that can also act as an internal base for the desired syn ‐selective elimination. To our delight, treating 22 with a stoichiometric amount of vanadyl acetylacetonate furnished the C2‐oxidized enamine 20 in 61 % yield as a major product. The formation of 20 connoted access to the C2‐iminium ion intermediate 29 through the vanadium‐mediated intramolecular syn elimination by a deprotonation at C2 of the intermediate 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these, the addition reaction of a carbon nucleophile to imines or iminium ions through Mannich-type reaction appears more useful (Scheme 1, reactions 1–3). However, these reactions need expensive arylboronic acids (Petasis reaction) [49] and suitable leaving groups [1012] as well as a metal catalyst (Polonovsky reaction; this route requires the preparation of amine N -oxide in advance) [1314]. …”
Section: Resultsmentioning
confidence: 99%